What do Chinese entrepreneurs think about entrepreneurship: A case study of popular essays on Zhisland - Zhenping Zhang; Haiyang Yang; Jiayin Qi (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Entrepreneurship is becoming increasingly essential in this current era of the knowledge economy. It contributes to the innovation of products and services as well as improved processes. In the long-run, it can also improve the sustainability of the economy by depicting better efficiency and social goals. To stimulate entrepreneurship, it is essential to investigate the thinking behind entrepreneurship or what entrepreneurs think about entrepreneurship. Such investigations should encompass the mental images of entrepreneurs. In this regard, content analysis, based on the popular Zhisland essays, may be applied to elicit opinions from Chinese entrepreneurs about activities, critical factors and intended outcomes within the ambit of entrepreneurship. In this study, 634 concepts are first coded and categorized into 20 second-level themes and six first-level themes. The six first-level themes are competing strategy, human resource management, management and leadership, marketing and sale, research and development, and risk management. Furthermore, among the 20 second-level themes, leadership, self-improvement, and the risk of business cycle attract the highest attention, each of which accounts for around 10% of the coded concepts. Finally, a causal loop diagram is depicted to synthesize the coding results. This study also underscores three essential activities of entrepreneurship, which entail building and maintaining competing advantage, improving user experience, and risk management. Entrepreneurs need to balance investments in those activities according to the change in environment and customers' needs.
Keywords: 650; entrepreneurship; entrepreneur; content analysis; causal loop diagram; system dynamics; mental image